(untitled) (Community Based Medical Journal, 2014)
Indoor air pollution from biomass smoke is now regarded as public health hazard in the developing world causing different respiratory diseases. A cross-sectional study was conducted to see the prevalence of respiratory disease and status of respiratory function among female biomass fuel users and gas/electricity fuel users in a selective area of Bangladesh. A total of 103 females from Madla, a rural area under Bogra District of Bangladesh, which having good communication facilities, meeting the defined enrollment criteria for biomass fuel group were selected purposively as cases, while 101 females from the urban households from Thanthania in the same district, meeting the defined eligibility criteria for controls were included in gas/electricity fuel group. The participants were interviewed on a semi-structured questionnaire from March to June 2007. Moreover, peak expiratory flow rate (PEFR) of 98 participants from each group was measured as a lung function parameter. In the biomass group, majority (61.6%) used open type of kitchen, 21.2% partially closed kitchen, 11.1% closed and 6.1% closed non-ventilated kitchen. Nearly three-quarter (73%) of the gas/electricity group used closed ventilated type of kitchen, 26% used partially closed kitchen and only 1 case used open kitchen. Nearly one-quarter (24%) of the biomass group had habit of taking beetle-nut compared to only 3% of the gas/electricity group and chewing tobacco was also revealed to be proportionately higher in the former group (22.8%) than that in the latter group (4%) (p<0.001). The biomass group exhibited a significantly higher frequency of respiratory problem (16.5%) compared to their gas/electricity counterpart (5%). 30.4% of the participants of biomass group suffered from allergic rhinitis as opposed to 13% of the gas/electricity group. Coughing was also significantly higher in the biomass group (13.7%) than that in the gas/electricity group (1%). Coughing in the early morning and cough with productive sputum also demonstrated their significant presence in the former group than that in the latter group. Peak expiratory flow rate (PEFR) shows that it was significantly lower in the biomass fuel user group (225.0±38.6 L/min.) than that of the gas/electricity user group (247.5±34.4 L/min.) (p<0.001). It was found that smoke generated from biomass fuel combustion is a significant risk factor for respiratory problems among the female household members who, by tradition, are associated with cooking activities. CBMJ 2014 January: Vol. 03 No. 01 P: 08-12